Congenital Abdominal Wall Defects: Staged closure by Dual Mesh - Kirsten Risby; Marianne Skytte Jakobsen; Niels Qvist (EL-Med-Pub, 2015)
Objective: To evaluate the clinical utility of GORE® DUALMESH (GDM) in the staged closure of large congenital abdominal wall defects. Materials and Methods: Data of patients with congenital abdominal wall defects managed with GDM was analyzed for outcome regarding complete fascial closure; mesh related complications; and post-discharge gastrointestinal surgery. Results: GDM was placed in 34 (gastroschisis=27, omphalocele=7) patients during the study period. Complete closure of the fascia was obtained in one patient with omphalocele and in 22 patients with gastroschisis. Mesh related surgical complications were seen in five (15%) children: four had detachment of the mesh and one patient developed abdominal compartment syndrome. Mesh related clinical infection was observed in five children. In hospital mortality occurred in four cases (2 gastroschisis and 2 omphalocele) and was not procedure-related. Of the 30 children discharged, 28 (82%) were still alive. At follow-up, three patients (10%) were operated for a minor ventral hernia and 4 children were operated (laparotomy and adhesionolysis) for adhesive intestinal obstruction. Conclusion: Staged closure with GDM is a safe alternative when primary fascial closure is difficult.